Tax Compliance: A Bibliometric Analysis of Global Research Trends (2000–2026) - Loso Judijanto; Khairul Nur Adli (West Science Accounting and Finance, 2026)
This study aims to examine the development, intellectual structure, and thematic evolution of taxation research using a bibliometric approach. Data were collected from the Scopus database and analyzed using VOSviewer to explore publication trends, keyword co-occurrence, and temporal dynamics of the field. The findings reveal that taxation research is predominantly centered on tax compliance, with significant attention given to issues such as tax evasion, tax avoidance, trust, and tax knowledge. Co-occurrence analysis identifies three major thematic clusters: behavioral aspects of tax compliance, policy and regulatory frameworks, and economic and interdisciplinary perspectives. The overlay visualization indicates a clear evolution from early research focused on regulatory compliance and environmental taxation toward more recent studies emphasizing taxpayer behavior and contextual factors, including developing countries. Furthermore, density analysis highlights tax compliance and taxation as the most influential and frequently studied topics, while emerging themes such as sustainability and artificial intelligence suggest new directions for future research. Overall, this study provides a comprehensive mapping of taxation literature and offers insights into how the field is evolving toward a more integrated and multidisciplinary perspective.